Historical review of the fiscal system (publ. at The Standard of Freedom Office, 1850)
Contains section XII(2 nd part)-XVI(1st part), continued from tract no. 30, to be continued in tract no. 32. - Issued by the Liverpool Financial Reform Association. - Authorship claimed by Alexander Somerville. - In pamphlet volume with covertitle: Tracts of the Liverpool Financial Reform Association.